2012
DOI: 10.1111/j.1442-2042.2012.03121.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of C‐reactive protein in urological cancers: A useful biomarker for predicting outcomes

Abstract: Abbreviations & AcronymsAbstract: Based on increasing evidence of the association between cancer-related inflammation and the progression of cancer, the external symptoms of systemic inflammatory response has been shown to be an indicator for the prognosis of many malignancies, including urological cancers. C-reactive protein, a representative acute-phase reactant, is a significant and sensitive inflammatory marker that can be objectively measured using reliable assays in clinical practice worldwide. C-reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…15 Patients with advanced RCC sometimes show paraneoplastic syndrome with fever and leukocytosis. The involvement of several molecules related to inflammation, such as interleukin-6 , 16 nuclear factor-kappa B, 17 and CRP, 10,11,13 on the progression of RCC have been previously demonstrated. A high NLR is associated with a poor prognosis in many solid tumours.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…15 Patients with advanced RCC sometimes show paraneoplastic syndrome with fever and leukocytosis. The involvement of several molecules related to inflammation, such as interleukin-6 , 16 nuclear factor-kappa B, 17 and CRP, 10,11,13 on the progression of RCC have been previously demonstrated. A high NLR is associated with a poor prognosis in many solid tumours.…”
Section: Discussionmentioning
confidence: 91%
“…8,9 Parameters of inflammatory response, such as C-reactive protein (CRP), have been reported as prognostic markers in urological cancers. [10][11][12] The implication of CRP for predicting the prognosis or the effect of agents has also been demonstrated with targeted therapy in RCC. 13 Besides CRP, the elevation of the neutrophils-to-lymphocytes ratio (NLR) has been reported as a prognostic factor in cancers, including RCC.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for patients with elevated CRP concentration is poor. The underlying inflammatory process related to cancer plays an important role in the progression of renal cell carcinoma (Saito and Kihara, 2013). On the one hand, immunotherapy, relying on the host mounting a cytotoxic immune response to the tumor, has shown a survival advantage for men with advanced prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the phagocytosis of apoptotic cells increases the level of anti-inflammatory mediators supporting Inflammatory responses are stopped following the removal of pathogens; however, they can persist in the case of chronic infection, resulting in tissue fibrosis and carcinogenesis by the establishment of adverse inflammatory cycles [66][67][68]. The characteristics of chronic inflammation are inflammatory foci directed by plasma cells, lymphocytes and macrophages, generating a high level of cytokines, growth factors, chemokines, nitrogen species and reactive oxygen, which may be responsible for incessant tissue damage [69,70].…”
Section: Gall Bladder Cancermentioning
confidence: 99%